Two new species of Oxytrechus Jeannel, 1927 (Coleoptera, Carabidae, Trechini) from Peru - Delgado, Pedro; Ruiz-Tapiador, Ildefonso (Zootaxa, 2019)
O. juani n. sp. and O. alexei n. sp. are described as new species of the genus Oxytrechus Jeannel, 1927, from the southeastern Peruvian Andes, at altitudes between 4,646 and 4,888 m.